Pengetahuan Dasar Gunung Api Menggunakan Komik Edukasi pada Anak-Anak Panti Asuhan Dharma Jati I Klungkung Provinsi Bali: Pengetahuan Dasar Gunung Api Menggunakan Komik Edukasi pada Anak-Anak Panti Asuhan Dharma Jati I Klungkung Provinsi Bali - Maharani, Nia (UNIB Press, 2025)
This research was a continuation of the research and community service activities (PKM) of the author and the service to society team in January - May 2023 at the same location, namely the Darma Jati I Klungkung Bali Orphanage. This research discusses how orphanage children know about volcanoes and their mitigation. The research results obtained from the questionnaire show that they still lack knowledge about volcanoes and their mitigation). For the reasons mentioned above, the author and the PKM team carried out outreach activities using brochures containing volcanoes and their mitigation to provide basic knowledge of volcanoes). The results of PKM activities show that the children at the orphanage understand enough about the dangers of volcanoes and their anticipation. In this follow-up research, researchers are trying to create educational comics about volcanoes and mitigation to make them more interesting and easy to understand. This comic comes from a brochure that was made previously. The comic was given to the children living in the orphanage with the aim that the children could take steps to take before, during, and after a volcanic eruption. The results of the final research questionnaire showed an increase in knowledge from before.